Condition and The Affecting Factors of Tanjung Jumlai Patch Reef in North Penajam Paser Regency East Kalimantan - Muchlis Efendi; Sahat Hutahaean; Anugrah A Budiarsa; T Hanjoko (Chemical Engineering Diponegoro University, 2014)
Patch reef of Tanjung Jumlai which located in North Penajam Paser Regency, East Kalimantan Province has being suffered from stress and degradation, less studied and managed. Thus, this research was conducted to obtain data concerning on the reef condition and the affecting factors. The research was carried out from December 10 – 14, 2013. There were eight observation stations that surveyed using life form line intercept transect method to obtain data related with coral reef condition based on percent cover of live coral (LC) and coral mortality index (MI). The result showed that the lowest LC was 5% at ST 7 (poor/bad coral condition) and the highest LC was 78% (excellent condition), and the average LC was 42.5% (fair/moderate condition). The average coral mortality index was 0.34 with the lowest MI was 0.06 at ST 6 and the highest MI was 0.78 at ST 7. This study also found that anthropogenic factors (mainly from Balikpapan Bay) were more influential toward the reef condition of Tanjung Jumlai patch reef rather than non-anthropogenic factors.